Characteristics Of Neologisms Created in The Epics of Independence - M. Kurbanova; Sh. Nuriddinova; F. Abdulhaeva. (Periodica Journal, 2022)
The given article is devoted to lingvopoetik research of the poems of the period of Independence. The Independence periods poems are analysed linguistically and literarily. The specific feauture of neologisms of Independence period are revealed.
Keywords: Lingvopoetik; Poems; Linguistically; Literarily